A novel approach to the application of hexagonal mesoporous silica in solid-phase extraction of drugs - Farjadian, Fatemeh (Heliyon, 2018)
Mesoporous silica with hexagonal type structure containing amine functional group was introduced. Firstly, aminopropyl hexagonal mesoporous silica was synthetized in a co-condensation process, via templating route of n-dodecylamine. Then synthesized mesoporous material were characterized, and FT-IR spectrum confirmed the presence of amine group and CHN analysis determined the amount of organic layer. The high surface area (750 m(2)/g) was determined by applying nitrogen adsorption-desorption technique. The morphology was examined by scanning electron microscopy which proved hexagonal structure. The crystallinity of mesoporous material was observed in XRD pattern of this material. According to previous background of such material in adsorbing drug, herein, the efficiency of this material in adsorbing of 5-fluorouracil was evaluated through solid phase extraction method in aqueous and plasma media with high performance liquid chromatography. The extraction efficiency was evaluated for drug concentrations of 500–2000 ng/ml by means of 5–20 mg/ml hexagonal mesoporous silica in both media. The results showed good to excellent recovery rate of in both aqueous and plasma medium which confirmed that the aminopropyl functionalized hexagonal mesoporous silica could be considered as promising device for drug bioanalysis.